Acute Tonsillitis: Causes, and Management - A Comprehensive Review (Homoeopathy for All, 2024)
Acute tonsillitis, characterized  by tonsil inflammation, poses  a significant health concern,  affecting diverse age groups and  socioeconomic backgrounds. This  comprehensive review synthesizes  various aspects of acute tonsillitis,  spanning its causes, epidemiological  trends, diagnostic advances, and  treatment strategies. Research  endeavours have illuminated the  condition's multifaceted nature,  revealing viral and bacterial  pathogens' roles and the intricacies  of host immune responses. Notably,  novel treatment avenues have  emerged, including alternative  therapies and antimicrobial agents  to combat antibiotic resistance.  Collaboration between medical  professionals and researchers has  led to evolving clinical guidelines  and innovative prevention  measures like vaccines. However,  research gaps persist, necessitating  further exploration of alternative  treatments, long-term outcomes,  optimal antibiotic use, genetic and  environmental factors, patient reported experiences, and advanced  prevention strategies. Continued  interdisciplinary research promises  to enhance our understanding  of acute tonsillitis, ultimately  improving patient care, reducing  complications, and bolstering  preventive measures, thereby  advancing public health outcomes.
Keywords: Tonsillitis; Management; Comprehensive